Clinical benefit, development, innovation, trials, epidemiology, and price for cancer drugs and indications with multiple special FDA designations - Michaeli, Daniel; Michaeli, Christoph T.; Albers, Sebastian; Michaeli, Julia (Journal of the National Cancer Institute, 2024)
This study analyzes the development, US Food and Drug Administration (FDA) approval, benefits, innovation, trials, epidemiology, and price of cancer drugs with multiple special designations: orphan, fast track, accelerated approval, priority review, and breakthrough therapy.In total, 355 FDA-approved cancer drug indications with 841 special designations were identified (2012-2022). Trial, epidemiology, and price data were collected from FDA labels, the Global Burden of Disease study, and Medicare and Medicaid. The association between efficacy outcomes and indications’ number of special designations were compared in meta-analyses.Median development times were 7.3, 7.8, and 5.4 months (P = .027) for drugs with 0 to 1, 2 to 3, and 4 to 5 special designations, respectively. Multiple special designations were associated with higher biotechnological and clinical innovation. Median patient enrollment in trials were 615, 471, 398, 168, 104, and 120 (P < .001) for indications with 0 to 5 special designations. Drugs for rare diseases supported by open-label phase 1/2 trials of single-arm design were granted more special designations. Hazard ratios for overall survival (0.80 vs 0.73 vs 0.73 vs 0.69 vs 0.56 vs 0.52; P = .003) and progression-free survival (0.70 vs 0.61 vs 0.59 vs 0.44 vs 0.37 vs 0.67; P < .001) substantially declined while tumor response increased with more special designations. Mean monthly prices increased for drugs with 0 to 4 but not 5 special designations ($21596 vs $14753 vs $32410 vs $41240 vs $38703 vs $19184).Multiple special designations are associated with faster clinical development and greater benefits for patients with unmet needs but also with nonrobust trial evidence and a tendency toward higher drug prices.